Development and pilot evaluation of an electronic health record usability and safety self-assessment tool. Issue 3 (30th July 2022) - Pruitt, Zoe; Howe, Jessica L; Krevat, Seth A; Khairat, Saif; Ratwani, Raj M
Abstract: Objective: Poor electronic health record (EHR) usability contributes to clinician burnout and poses patent safety risks. Site-specific customization and configuration of EHRs require individual EHR system usability and safety testing which is resource intensive. We developed and pilot-tested a self-administered EHR usability and safety assessment tool, focused on computerized provider order entry (CPOE), which can be used by any facility to identify specific issues. In addition, the tool provides recommendations for improvement. Materials and Methods: An assessment tool consisting of 104 questions was developed and pilot-tested at 2 hospitals, one using a Cerner EHR and the other using Epic. Five physicians at each site participated in and completed the assessment. Participant response accuracy compared to actual EHR interactions, consistency across participants, and usability issues identified through the tool were measured at each site. Results: Across sites, participants answered an average of 46 questions in 23 min with 89.9% of responses either correct or partially correct. The tool identified 8 usability and safety issues at one site and 7 at the other site across medication, laboratory, and radiology CPOE functions. Discussion: The tool shows promise as a method to rapidly evaluate EHR usability and safety and provide guidance on specific areas for improvement. Important improvements to the evaluation tool were identified including the need to clarify certain questions and provide definitions for usability terminology. Conclusion: A self-administered usability and safety assessment tool can serve to identify specific usability and safety issues in the EHR and provide guidance for improvements. Lay Summary: Electronic health records (EHRs) can improve care delivery by making it easier to access important patient information and by expediting the ordering of medications, laboratory tests, and diagnostic images, among other benefits. However, the usability of these software systems, which is defined as how efficiently, effectively, and satisfactorily the technology can be used, has been a longstanding challenge for most healthcare facilities. These usability challenges have direct patient safety consequences and can lead to patient harm. To help healthcare facilities identify specific EHR usability and safety challenges we developed a self-assessment tool. The self-assessment tool can be used by any healthcare facility, regardless of level of usability knowledge, to identify specific usability and safety challenges. The tool provides specific guidelines for how to address identified issues. We pilot-tested the self-assessment tool at 2 different healthcare systems and identified numerous usability issues at each site. Opportunities to improve the tool were identified. This type of self-assessment tool shows tremendous promise as a low-cost and scalable method to identify and address usability and safety challenges.